A Nonlocal Multipoint Problem for a System of Fourth-Order Partial Differential Equations - Assanova, Anar; Tokmurzin, Zhanibek (Eurasian Mathematical Journal, 2020)
A nonlocal multipoint problem for a system of fourth-order partial differential equations is investigated. Based on the results obtained for a family of multipoint boundary value problems with an integral condition for a system of ordinary integro-differential equations, conditions for the existence of classical solutions of a nonlocal multipoint problem for a fourth-order partial differential equation system are established.